OPTIMALISASI MANAJEMEN PEMASARAN PRODUK UMKM MELALUI BRANDING DAN SEGMENTASI PASAR DI PAUH, KOTA PADANG - Howardi Visza Adha; David Malik; Harry Wahyudi; Amrullah Amrullah; Edi Suandi; Mya Yuwanita Suhanda (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
This community service program aims to optimize the marketing management of MSME products by strengthening branding and market segmentation in Pauh District, Padang City. MSMEs in this region have significant potential to support the local economy, but still face marketing challenges, particularly weak brand identity, inaccurate target market determination, and limited planned, consumer-needs-based marketing strategies. Some businesses still market their products conventionally without understanding the characteristics of appropriate market segments, thus limiting their competitiveness and market reach. Furthermore, product branding is inconsistent in terms of name, packaging, and promotional messages, resulting in under-development of product added value. This program is implemented using a participatory and applied approach through initial condition identification, marketing management training, mentoring to strengthen branding, and the implementation of market segmentation relevant to local conditions. Methods used include interactive lectures, discussions, hands-on practice, and monitoring and evaluation. The expected outcomes are increased capacity of MSMEs in marketing management, the formation of a strong brand identity, clear market segmentation, and increased competitiveness and sustainable product sales